2022
DOI: 10.3389/fmars.2022.821478
|View full text |Cite
|
Sign up to set email alerts
|

A Multi-Tissue, Multi-Species Assessment of Lipid and Urea Stable Isotope Biases in Mesopredator Elasmobranchs

Abstract: The application of stable isotope analysis (SIA) is increasing in elasmobranch trophic ecology, but inconsistency remains in terms of the tissue pre-treatment methods chosen to remove biases introduced by lipids and urea. SIA of a range of non-lethally extracted tissues from a diverse group of elasmobranchs, including mesopredators, is increasing, yet most studies assume that isotope biases from lipid and urea are the same across tissues and species. To determine tissue- and species-specific isotope biases acr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 82 publications
0
10
0
Order By: Relevance
“…Lipids and urea in whale shark dermal tissues can lower δ 13 C and δ 15 N values [48], leading to bias in analyses. To remove urea, dermal tissue samples were submerged in 1.4 mL of deionized water in 1.5 mL Eppendorf tubes, vortexed for 5 min, and placed in a 30 • C water bath for 24 h. Eppendorf tubes were then removed from the water bath, centrifuged at 2000 rpm for 10 min, and the excess water decanted.…”
Section: Methodsmentioning
confidence: 99%
“…Lipids and urea in whale shark dermal tissues can lower δ 13 C and δ 15 N values [48], leading to bias in analyses. To remove urea, dermal tissue samples were submerged in 1.4 mL of deionized water in 1.5 mL Eppendorf tubes, vortexed for 5 min, and placed in a 30 • C water bath for 24 h. Eppendorf tubes were then removed from the water bath, centrifuged at 2000 rpm for 10 min, and the excess water decanted.…”
Section: Methodsmentioning
confidence: 99%
“…Fifty samples of seven reference materials were used for d 13 C, and 54 samples of eight reference materials for d 15 N. Results are expressed in the delta (d) notation as per mil (‰), so that: dX = (R sample /R standard -1) × 10 3 , where dX is the stable isotope composition of the sample, R sample is our sample's molar ratio of the heavy to light element, and R standard that ratio in the international standard material. Lipids and urea were not extracted from shark samples prior to analysis, because lipid/urea treatments can influence d 13 C and d 15 N, and magnitude and direction of this effect is variable among studies, taxa, and tissues (e.g., Carlisle et al, 2017;Crook et al, 2019;Bennett-Williams et al, 2022). Also, it has recently been shown that lipid/urea extraction does not significantly affect elasmobranch muscle d 13 C (Bennett- Williams et al, 2022).…”
Section: Stable Isotope Analysismentioning
confidence: 99%
“…Lipids and urea were not extracted from shark samples prior to analysis, because lipid/urea treatments can influence d 13 C and d 15 N, and magnitude and direction of this effect is variable among studies, taxa, and tissues (e.g., Carlisle et al, 2017;Crook et al, 2019;Bennett-Williams et al, 2022). Also, it has recently been shown that lipid/urea extraction does not significantly affect elasmobranch muscle d 13 C (Bennett- Williams et al, 2022).…”
Section: Stable Isotope Analysismentioning
confidence: 99%
“…Understanding the effects of treatments ET and ET+LE on predator muscle tissue stable isotope values is valuable for accurately interpreting data in food-web studies. Removing these biases is essential for acquiring standardized stable isotope values among different species, and a reasonable adjustment could be helpful for the use of the valuable biopsy samples obtained from remote areas and archived collections (Kim and Koch, 2012;Li et al, 2016;Bennett-Williams et al, 2022). In this study, the results for twelve pelagic predators suggested that both treatments ET and ET+LE caused inconsistent effects in d 13 C, d 15 N values, and C/N ratios during the 28 days of preservation and then could remain stable throughout the experiment, yielding new insights into the effects of these treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Since the effects of treatment ET on muscle d 13 C and d 15 N values of marine organisms were reported to be variable and inconsistent among species, conducting SIA directly using treatment ET samples was not recommended (Barrow et al, 2008;Boecklen et al, 2011;Kim and Koch, 2012). In addition, lipid extraction (LE) was recommended as a standardization step prior to SIA since lipids were 13 C-depleted relative to proteins and carbohydrates and could potentially cause the d 13 C values of organisms to be negatively biased relative to their diet with increasing lipid content (Wessels and Hahn, 2010;Elliott and Elliott, 2016;Li et al, 2016;Bennett-Williams et al, 2022). However, there was less evidence to indicate whether treatment LE affected the stable isotope values of treatment ET samples.…”
Section: Introductionmentioning
confidence: 99%